Linear Parameter-Varying Versus Linear Time-Invariant Reduced-Order Controller Design for Turboprop Aircraft Dynamics - Widowati, Widowati; Riyanto, Bambang; Muhammad, Hari (Journal of Engineering and Technological Sciences, 2012)
TheÂ  applicabilityÂ  ofÂ  parameter-varyingÂ  reduced-orderÂ  controllersÂ  to aircraftÂ  modelsÂ  isÂ  proposed.Â  AÂ  generalizationÂ  ofÂ  theÂ  balancedÂ  singular perturbation method of the linear time-invariant (LTI) system was used to reduce the order ofÂ  theÂ  linear parameter-varying (LPV) system. Based on the reducedorder model, aÂ  low-orderÂ  LPVÂ  controllerÂ  wasÂ  designedÂ  usingÂ  the Hâ synthesis technique.Â  TheÂ  performanceÂ  ofÂ  theÂ  reduced-orderÂ  controllerÂ  wasÂ  examinedÂ  by applyingÂ  itÂ  toÂ  theÂ  lateral-directionalÂ  controlÂ  ofÂ  aÂ  20th-orderÂ  aircraftÂ  model. Furthermore, the time responses of the closed-loop system withÂ  several reducedorder LPV controllers andÂ  aÂ  reduced-order LTI controllerÂ  wereÂ  compared.Â  The simulation resultsÂ  show that anÂ  ,Â  8th -order LPV controller can maintain stability andÂ  provideÂ  theÂ  sameÂ  levelÂ  ofÂ  closed-loopÂ  systemÂ  performanceÂ  asÂ  aÂ  full-order LPVÂ  controller.Â  ThisÂ  wasÂ  notÂ  theÂ  caseÂ  withÂ  theÂ  reduced-orderÂ  LTIÂ  controller, whichÂ  cannotÂ  maintainÂ  stabilityÂ  andÂ  performanceÂ  forÂ  allÂ  allowableÂ  parameter trajectories.